TEORI DASAR METODE STUDI ISLAM: (Pembacaan atas Pemikiran Charles J. Adams dan Richard C. Martin) - Afiful Ikhwan (P3M IAI Nusantara Batang Hari, 2015)
In looking at and defining the Islamic religion, Adams using the theoretical framework of Wilfred Cantwell Smith distinguishes between Tradition and Faith. Aspects of faith is to understand and appreciate the personal experience and the real behavior of a person. Aspects of the tradition that the external aspects of religious, social and historical aspects of religion that can be observed in the community. Adam approaches to approach aspects of life in individuals and religious communities is twofold: Normative approach and descriptive approach. Normative approach is the approach that is inspired by the motivation and religious purposes, while the descriptive approach emerged as a response to the intellectual curiosity or academic motivation.